A preparation method of super interference iron red gold fantasy pearlescent pigment
Through the process of alternating multi-layer coating of high and low refractive index substances, combined with the coating process of bismuth oxychloride compounds, iron manganese compounds, silicon oxides and titanium zinc compounds, the existing gold pearlescent pigments have been solved in color saturation and brightness. The degree and metal texture are insufficient to produce super-strong interference iron red gold color pearlescent pigment with significant optical interference effect and high hiding power.
Patent Information
- Application Number
- CN202310313179.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-03-28
AI Technical Summary
The existing gold pearlescent pigments are not as good as ordinary gold pigments in terms of color saturation, brightness, metal texture and hiding power. The process is complex and the safety risks are great, making it difficult to take into account the green and red phases in gold.
The substrate slurry is coated with bismuth oxychloride compound, iron manganese compound, silicon oxide, second bismuth oxychloride compound and titanium zinc compound by alternate multi-layer coating process, and Calcination is carried out to produce super-strong interferometric iron-red gold illusion pearlescent pigment.
It significantly enhances the optical interference effect of the pigment, improves color saturation, brightness and hiding power, and perfectly blends the green phase and red phase in the golden pearlescent pigment, with better metal texture and safety.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of preparation of golden pearlescent pigments, in particular to a method for preparing super-interference iron red gold fantasy color pearlescent pigments. Background Art
[0002] Gold always gives people a sense of elegance and luxury. If an object is given gold, then words such as high-end, value, grandeur, and sacredness will become its labels. The wheel of human aesthetic level has never stopped, and the development of gold pigments has always been on the road. Before the rise of pearlescent pigments, people mainly relied on copper-gold powder to obtain gold powder materials with metallic texture. Copper-gold powder is made of copper-zinc alloy as raw material. It is a kind of metal pigment with flaky structure, floating in the binder, showing golden luster, and pigment properties after special mechanical processing and surface chemical treatment. Its production process has safety hazards such as flammability and explosion; and if copper-gold powder is used to package children's toys, there is a risk of children accidentally ingesting it, thereby causing heavy metal poisoning. For the above reasons, the application of copper-gold powder is limited. Instead, it is replaced by gold pearlescent pigments based on inorganic non-metallic materials-natural mica. By coating a certain thickness of titanium dioxide on the surface of mica using the sol-gel method, it can obtain the flash effect of metallic pigments and produce gold pearlescent pigments with a soft color like natural pearls. Although this method is simple, the golden pearlescent pigment produced is still far from real gold in terms of color saturation, brightness, metallic texture, etc.
[0003] Guangdong Weino Pearlescent Pigment Co., Ltd. uses a four-layer coating "synthetic mica / AlCl3*SnCl4 / TiCl4 / FeCl3*ZnCl2 / TiCl4" process in patent CN102127321A to produce golden pearlescent pigments, but the process involves many types of hydrolyzed compounds, and the batching work before hydrolysis and coating is cumbersome and complicated, which is prone to errors; Hangzhou Fuwode Fine Chemical Co., Ltd. uses a five-layer coating "SnCl4 / TiCl4 / Na2SiO3 / AlCl3 / TiCl4" process in patent CN104098931A to produce golden pearlescent pigments. Although the golden pearlescent pigments produced by this process have greatly improved in brightness compared with ordinary golden pigments, they have a heavy green phase in hue, giving people a cold feeling, ignoring the passionate feeling that gold itself brings to people, and the role and necessity of AlCl3 in this process remain to be studied; Fujian Kuncai Materials Technology Co., Ltd. uses a five-layer coating "SnCl4 / TiCl4 / Na2SiO3 / AlCl3 / TiCl4" process in patent CN108 The gold pigment obtained by the five-layer coating process of "SnCl4 / TiCl4*CoCl2 / Na2SiO3*FeCl3 / TiCl4*CoCl2 / FeCl3" in 752978A also focuses too much on the expression of the green phase in gold, and the amount of compounds added to the suspension in this process is too large, which is a challenge for the mica coating rate and the calcination process in the post-treatment process. In other words, due to the limited mica coating rate, the added compounds cannot completely produce effective coating, and some hydrolyzed substances exist in the reaction liquid phase in a free state, which will not only affect the coating effect, but also cause waste of raw materials. At the same time, a large amount of coating on the surface of the mica substrate increases the risk of damage to the structural layer in the calcination process. In addition, in the third layer of coating, the article proposes to use FeCl3 to balance the pH of Na2SiO3 during hydrolysis and the entire system is an acidic environment, which will cause Na2SiO3 hydrolysis to be unstable, affecting the coating effect and thus affecting the product quality.
[0004] Therefore, it is of great prospect to research and develop a method for preparing super interference iron red gold fantasy pearlescent pigment which has simple process, safety, stability, suitability for industrial production, and can take into account both the green and red phases in gold, and whose color saturation, brightness, metallic texture and hiding power are far higher than those of ordinary gold pigments on the market. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a super interference iron red gold fantasy color pearlescent pigment in view of the deficiencies in the prior art.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a method for preparing a super interference iron red gold fantasy pearlescent pigment. The method comprises the following steps: coating a substrate slurry with a first chlorine oxybismuth compound, an iron manganese compound, a silicon oxide, a second chlorine oxybismuth compound and a titanium zinc compound in sequence; and calcining the coated substrate slurry to obtain the super interference iron red gold fantasy pearlescent pigment.
[0008] Preferably, the volume concentration of the substrate slurry is 7-15%.
[0009] Preferably, the first bismuth oxychloride compound coating is to add BiCl3 solution to the substrate slurry for reaction, the temperature of the substrate slurry is 70-90°C, the pH value is 0.5-2.0, the concentration of the BiCl3 solution is 0.04-0.06 mol / L, the reaction time is 25-35 min, the time for adding the BiCl3 solution is 120-150 min, and the mass ratio of the substrate slurry to the BiCl3 solution is 40-50:45-55.
[0010] Preferably, the iron-manganese compound coating is performed by adding a manganese-iron mixed solution to the substrate slurry after the first bismuth oxychloride compound coating for reaction, the temperature of the substrate slurry after the first bismuth oxychloride compound coating is 60-90°C, the pH value is 2.0-4.0, and the reaction time is 25-35 minutes.
[0011] Preferably, in the ferromanganese mixed solution, the volume ratio of MnCl2 solution to FeCl3 solution is 25-35:155-195, wherein the concentration of MnCl2 solution is 1.5-1.7 mol / L, and the concentration of FeCl3 solution is 1.7-1.9 mol / L; the volume mass ratio of the ferromanganese mixed solution to the substrate slurry is 180-230 mL:40-50 g.
[0012] Preferably, the silicon oxide coating is performed by adding a sodium silicate solution to the substrate slurry coated with the iron-manganese compound for reaction, the temperature of the substrate slurry coated with the iron-manganese compound is 70-85° C., the pH value is 7.5-9.5, the mass fraction of the sodium silicate solution is 12-16%, and the reaction time is 25-35 min; the mass volume ratio of the substrate slurry to the sodium silicate solution is 40-50 g: 230-280 mL.
[0013] Preferably, the second bismuth oxychloride compound coating is to add BiCl3 solution to the substrate slurry after coating the silicon oxide for reaction, the temperature of the substrate slurry after coating the silicon oxide is 80-95°C, the pH value is 0.5-1.5, the concentration of BiCl3 solution is 0.02-0.04 mol / L, the reaction time is 25-35 min, the addition time of BiCl3 solution is 60-90 min; the mass ratio of substrate slurry and BiCl3 solution is 40-50:45-55.
[0014] Preferably, the titanium zinc compound coating is performed by adding a titanium zinc mixed solution to the substrate slurry after the second bismuth oxychloride compound coating to react, the temperature of the substrate slurry after the second bismuth oxychloride compound coating is 65-85°C, the pH value is 1.0-2.0, and the reaction time is 25-35 minutes.
[0015] Preferably, in the titanium-zinc mixed solution, the volume ratio of TiCl4 solution to ZnCl2 solution is 155-180:24-30, wherein the concentration of TiCl4 solution is 1.6-1.8 mol / L, and the concentration of ZnCl2 solution is 1.8-2.0 mol / L; the volume mass ratio of the titanium-zinc mixed solution to the substrate slurry is 179-210 mL:40-50 g.
[0016] Preferably, the calcination temperature is 700-900° C., and the calcination time is 8-12 min.
[0017] The beneficial effects of the present invention include the following:
[0018] 1) Different metal oxides have different refractive indices. The present invention adopts a process of alternating multiple layers of high and low refractive index materials and controls the coating amount of each layer of materials to obtain a pigment that not only significantly enhances the optical interference effect, but also significantly increases the color saturation, brightness and hiding power of the pigment itself.
[0019] 2) The super interference iron red gold fantasy pearlescent pigment prepared by the present invention not only retains the green phase gold element in the golden pearlescent pigment, but also creates a warm atmosphere of red in the white background in the golden color, so that the green phase and the red phase in the golden pearlescent pigment are perfectly integrated and complement each other.
[0020] 3) The present invention mixes MnCl2 solution and FeCl3 solution in a certain ratio and then coats the iron-manganese compound, which greatly shortens the process flow and saves production costs. At the same time, a new red-yellow hue appears during the coating process.
[0021] 4) The present invention uses BiCl3 as the raw material for coating the bismuth oxychloride compound, which can enable the pigment to obtain better glossiness.
[0022] 5) The present invention mixes TiCl4 solution and ZnCl2 solution in a certain ratio and then coats the titanium zinc compound, which greatly shortens the process flow and saves production costs. At the same time, the introduction of ZnCl2 can effectively increase the hiding power and metallic texture of the product. DETAILED DESCRIPTION
[0023] The invention provides a method for preparing a super interference iron red gold fantasy pearlescent pigment. The method comprises the following steps: coating a substrate slurry with a first chlorine oxybismuth compound, an iron manganese compound, a silicon oxide, a second chlorine oxybismuth compound and a titanium zinc compound in sequence; and calcining the coated substrate slurry to obtain the super interference iron red gold fantasy pearlescent pigment.
[0024] In the present invention, the volume concentration of the base material slurry is preferably 7 to 15%, more preferably 9 to 13%, and even more preferably 10 to 12%.
[0025] In the present invention, the substrate slurry is preferably prepared by mixing a substrate and deionized water; the substrate is preferably synthetic mica, natural mica or glass flakes, and the particle size of the substrate is preferably 10 to 150 μm, more preferably 50 to 100 μm, and more preferably 60 to 80 μm.
[0026] In the present invention, the first bismuth oxychloride compound coating is preferably performed by adding a BiCl3 solution to a substrate slurry for reaction, and the temperature of the substrate slurry is preferably 70 to 90°C, more preferably 75 to 85°C, and more preferably 80°C; the pH value is preferably 0.5 to 2.0, more preferably 1.0 to 1.5, and more preferably 1.2 to 1.4; the concentration of the BiCl3 solution is preferably 0.04 to 0.06 mol / L, more preferably 0.045 to 0.055 mol / L, and more preferably 0.05 mol / L; the reaction time is preferably 25 to 35 min, more preferably 28 to 32 min, and more preferably 30 min; the time for adding the BiCl3 solution is preferably 120 to 150 min, more preferably 125 to 135 min, and more preferably 130 min; the mass ratio of the substrate slurry to the BiCl3 solution is preferably 40 to 50:45 to 55, more preferably 42 to 48:48 to 52, and more preferably 44 to 46:50.
[0027] In the present invention, hydrochloric acid is preferably used to adjust the pH value of the substrate slurry before coating, and the mass fraction of the hydrochloric acid is preferably 12 to 15%, more preferably 13 to 14%, and more preferably 13.5%.
[0028] In the present invention, the iron-manganese compound coating is preferably performed by adding a manganese-iron mixed solution to the substrate slurry after the first bismuth oxychloride compound coating to react. The temperature of the substrate slurry after the first bismuth oxychloride compound coating is preferably 60-90°C, more preferably 70-80°C, and more preferably 72-76°C; the pH value is preferably 2.0-4.0, more preferably 2.5-3.5, and more preferably 3.0; the reaction time is preferably 25-35min, more preferably 28-32min, and more preferably 30min.
[0029] In the ferromanganese mixed solution of the present invention, the volume ratio of MnCl2 solution to FeCl3 solution is preferably 25-35:155-195, more preferably 28-32:165-185, and more preferably 30:170-180; wherein, the concentration of MnCl2 solution is preferably 1.5-1.7 mol / L, more preferably 1.55-1.65 mol / L, and more preferably 1.6 mol / L; the concentration of FeCl3 solution is preferably 1.7-1.9 mol / L, more preferably 1.75-1.85 mol / L, and more preferably 1.8 mol / L; the volume mass ratio of the ferromanganese mixed solution to the substrate slurry is preferably 180-230 mL:40-50 g, more preferably 190-220 mL:42-48 g, and more preferably 200-210 mL:44-46 g.
[0030] In the present invention, it is preferred to use sodium hydroxide solution to adjust the pH value of the substrate slurry after the first bismuth oxychloride compound is coated, and the mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%; the time for adjusting the pH value is preferably 90-120min, more preferably 95-110min, and more preferably 100-105min.
[0031] In the present invention, sodium hydroxide solution is preferably used to balance the pH value of the reaction system during the iron-manganese compound coating process. The mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%.
[0032] In the present invention, the silicon oxide coating is preferably prepared by adding a sodium silicate solution to the substrate slurry coated with the iron-manganese compound for reaction. The temperature of the substrate slurry after coating the iron-manganese compound is preferably 70-85°C, more preferably 75-80°C, and more preferably 78°C; the pH value is preferably 7.5-9.5, more preferably 8-9, and more preferably 8.5; the mass fraction of the sodium silicate solution is preferably 12-16%, more preferably 13-15%, and more preferably 14%; the reaction time is preferably 25-35min, more preferably 28-32min, and more preferably 30min; the mass volume ratio of the substrate slurry to the sodium silicate solution is preferably 40-50g:230-280mL, more preferably 42-48g:240-270mL, and more preferably 44-46g:250-260mL.
[0033] In the present invention, it is preferred to use sodium hydroxide solution to adjust the pH value of the substrate slurry after coating the iron-manganese compound. The mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%.
[0034] In the present invention, hydrochloric acid is preferably used to balance the pH value of the reaction system during the silicon oxide coating process. The mass fraction of the hydrochloric acid is preferably 5-10%, more preferably 6-9%, and more preferably 7-8%.
[0035] In the present invention, the second bismuth oxychloride compound coating is preferably to add the BiCl3 solution to the substrate slurry after the silicon oxide is coated to react, and the temperature of the substrate slurry after the silicon oxide is coated is preferably 80 to 95°C, more preferably 82 to 90°C, and more preferably 84 to 86°C; the pH value is preferably 0.5 to 1.5, more preferably 1 to 1.5, and more preferably 1.2 to 1.5; the concentration of the BiCl3 solution is preferably 0.02 to 0.04 mol / L, and more preferably 0.025 to 0.0 .035mol / L, more preferably 0.03mol / L; the reaction time is preferably 25-35min, more preferably 28-32min, more preferably 30min; the addition time of BiCl3 solution is preferably 60-90min, more preferably 65-85min, more preferably 70-80min; the mass ratio of substrate slurry and BiCl3 solution is preferably 40-50:45-55, more preferably 42-48:48-52, more preferably 44-46:50.
[0036] In the present invention, it is preferred to use hydrochloric acid to adjust the pH value of the substrate slurry after the silicon oxide is coated. The mass fraction of hydrochloric acid is preferably 5-10%, more preferably 6-9%, and more preferably 7-8%; the time for adjusting the pH value is preferably 60-90 min, more preferably 70-80 min, and more preferably 75 min.
[0037] In the present invention, preferably, sodium hydroxide solution is used to balance the pH value of the reaction system during the second bismuth oxychloride compound coating process, and the mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%.
[0038] In the present invention, the titanium zinc compound coating is preferably performed by adding a titanium zinc mixed solution to the substrate slurry after the second bismuth oxychloride compound coating to react. The temperature of the substrate slurry after the second bismuth oxychloride compound coating is preferably 65-85°C, more preferably 70-80°C, and more preferably 74-76°C; the pH value is preferably 1.0-2.0, more preferably 1.2-1.8, and more preferably 1.4-1.6; the reaction time is preferably 25-35min, more preferably 28-32min, and more preferably 30min.
[0039] In the present invention, in the titanium-zinc mixed solution, the volume ratio of TiCl4 solution to ZnCl2 solution is preferably 155-180:24-30, more preferably 160-175:26-28, and more preferably 170:27; wherein the concentration of TiCl4 solution is preferably 1.6-1.8 mol / L, more preferably 1.65-1.75 mol / L, and more preferably 1.7 mol / L; the concentration of ZnCl2 solution is preferably 1.8-2.0 mol / L, more preferably 1.85-1.95 mol / L, and more preferably 1.9 mol / L; the volume mass ratio of the titanium-zinc mixed solution to the substrate slurry is preferably 179-210 mL:40-50 g, more preferably 182-200 mL:42-48 g, and more preferably 185-195 mL:44-46 g.
[0040] In the present invention, it is preferred to use sodium hydroxide solution to adjust the pH value of the substrate slurry after the second bismuth oxychloride compound coating, and the mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%; the time for adjusting the pH value is preferably 90-120min, more preferably 100-110min, and more preferably 105min.
[0041] In the present invention, sodium hydroxide solution is preferably used to balance the pH value of the reaction system during the titanium zinc compound coating process. The mass fraction of the sodium hydroxide solution is preferably 14-18%, more preferably 15-17%, and more preferably 16%.
[0042] In the present invention, it is preferred to filter the substrate slurry after coating to obtain a filter cake, and then the filter cake is washed and dried in sequence. The washing agent is preferably deionized water, and the drying temperature is preferably 80-120°C, more preferably 90-110°C, and more preferably 100°C; the role of washing is to wash out the soluble salts in the substrate slurry, and the moisture content of the filter cake after drying is preferably 0.1-0.8%, more preferably 0.3-0.6%, and more preferably 0.4-0.5%.
[0043] In the present invention, the calcination temperature is preferably 700-900°C, more preferably 750-850°C, and more preferably 800°C; the calcination time is preferably 8-12 min, more preferably 9-11 min, and more preferably 10 min.
[0044] In the present invention, after the substrate slurry after coating is calcined, it is preferably cooled, cleaned and dried in sequence to obtain a super interference iron red gold fantasy pearlescent pigment; the cooling temperature is preferably 20-30°C, more preferably 22-28°C, more preferably 24-26°C, the cleaning reagent is preferably deionized water, the drying temperature is preferably 100-110°C, more preferably 105°C, the drying time is preferably 2.5-3.5h, more preferably 2.8-3.2h, more preferably 3h.
[0045] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0046] Example 1
[0047] 40 g of synthetic mica with a particle size of 40 μm was placed in a 500 mL beaker and prepared into a substrate slurry with a volume concentration of 7% with deionized water. The temperature of the substrate slurry was adjusted to 70°C and the pH value was adjusted to 0.8 (the pH value was adjusted using 12% hydrochloric acid by mass), and then 45 g of a 0.05 mol / L BiCl3 solution was uniformly added to the substrate slurry through a constant flow pump (the time for adding the BiCl3 solution was 120 min) and reacted for 30 min to obtain the substrate slurry after the first bismuth oxychloride compound was coated.
[0048] After the temperature of the substrate slurry after the first bismuth oxychloride compound coating was adjusted to 60°C and the pH value was adjusted to 2.0 (the pH value was adjusted by a 16% sodium hydroxide solution by mass, and the time for adjusting the pH value from 0.8 to 2.0 was 90 min), 35 mL of a mixed solution of a 1.65 mol / L MnCl2 solution and 195 mL of a 1.8 mol / L FeCl3 solution was uniformly added to the substrate slurry after the first bismuth oxychloride compound coating through a constant flow pump and reacted for 30 min (a 16% sodium hydroxide solution by mass was used to balance the pH value of the reaction system during this coating process) to obtain a substrate slurry coated with an iron-manganese compound.
[0049] The temperature of the substrate slurry after coating the iron-manganese compound was adjusted to 70°C, and the pH value was adjusted to 8.0 (the pH value was adjusted using a 16% by mass sodium hydroxide solution). Then, 280 mL of a 12% by mass sodium silicate solution was uniformly added to the substrate slurry after coating the iron-manganese compound through a constant flow pump to react for 30 minutes (5% by mass hydrochloric acid was used to balance the pH value of the reaction system during the coating process) to obtain the substrate slurry coated with silicon oxide.
[0050] After the temperature of the substrate slurry after coating the silicon oxide is adjusted to 80°C and the pH value is adjusted to 1.0 (the pH value is adjusted by 6% hydrochloric acid by mass, and the time for adjusting the pH value from 8.0 to 1.0 is 60 minutes), 50g of BiCl3 solution with a concentration of 0.03mol / L is uniformly added (the time for adding the BiCl3 solution is 60 minutes) to the substrate slurry after coating the silicon oxide by a constant flow pump and reacted for 30 minutes (a sodium hydroxide solution with a mass fraction of 16% is used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry after coating the second oxychloride bismuth compound.
[0051] After the temperature of the substrate slurry after the second coating of the bismuth oxychloride compound was adjusted to 82°C and the pH value was adjusted to 1.2 (the pH value was adjusted by a 16% mass fraction sodium hydroxide solution, and the time for adjusting the pH value from 1.0 to 1.2 was 100 min), a mixture of 180 mL of a 1.7 mol / L TiCl4 solution and 30 mL of a 1.9 mol / L ZnCl2 solution was uniformly added to the substrate slurry after the second coating of the bismuth oxychloride compound through a constant flow pump and reacted for 30 min (a 16% mass fraction sodium hydroxide solution was used to balance the pH value of the reaction system during this coating process) to obtain a substrate slurry coated with a titanium zinc compound.
[0052] The substrate slurry after coating the titanium zinc compound is filtered to obtain a filter cake. The filter cake is washed with deionized water, and then dried in an oven at 80°C to a moisture content of 0.2%. The filter cake is then calcined in a muffle furnace at 800°C for 10 minutes. The calcined material is then cooled to 25°C, washed with deionized water, and finally dried at 100°C for 3.5 hours to obtain a super interference iron red gold fantasy pearlescent pigment.
[0053] Example 2
[0054] 40 g of glass flakes with a particle size of 10 μm are placed in a 500 mL beaker and prepared into a substrate slurry with a volume concentration of 15% with deionized water. The temperature of the substrate slurry is adjusted to 85°C and the pH value is adjusted to 1.0 (the pH value is adjusted using 13.5% hydrochloric acid by mass). Then, 50 g of 0.04 mol / L BiCl3 solution is uniformly added to the substrate slurry through a constant flow pump (the time for adding the BiCl3 solution is 125 min) and reacted for 25 min to obtain the substrate slurry after the first bismuth oxychloride compound coating.
[0055] After the temperature of the substrate slurry after the first bismuth oxychloride compound coating was adjusted to 70°C and the pH value was adjusted to 3.2 (the pH value was adjusted by a 14% sodium hydroxide solution by mass, and the time for adjusting the pH value from 1.0 to 3.2 was 100 min), 30 mL of a 1.55 mol / L MnCl2 solution and 160 mL of a 1.7 mol / L FeCl3 solution were added to the substrate slurry after the first bismuth oxychloride compound coating at a uniform speed through a constant flow pump to react for 35 min (a 14% sodium hydroxide solution was used to balance the pH value of the reaction system during this coating process) to obtain a substrate slurry coated with an iron-manganese compound.
[0056] After the temperature of the substrate slurry after coating the iron-manganese compound was adjusted to 80°C and the pH value was adjusted to 8.2 (the pH value was adjusted using a 14% sodium hydroxide solution by mass), 265 mL of a 14% sodium silicate solution by mass was uniformly added to the substrate slurry after coating the iron-manganese compound through a constant flow pump to react for 32 minutes (8% hydrochloric acid by mass was used to balance the pH value of the reaction system during the coating process) to obtain the substrate slurry coated with silicon oxide.
[0057] After the temperature of the substrate slurry after coating the silicon oxide is adjusted to 85°C and the pH value is adjusted to 1.0 (the pH value is adjusted by 8% hydrochloric acid by mass, and the time for adjusting the pH value from 8.2 to 1.0 is 65 minutes), 45g of BiCl3 solution with a concentration of 0.02mol / L is uniformly added (the time for adding the BiCl3 solution is 65 minutes) to the substrate slurry after coating the silicon oxide by a constant flow pump and reacted for 25 minutes (a sodium hydroxide solution with a mass fraction of 14% is used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry after coating the second bismuth oxychloride compound.
[0058] After the temperature of the substrate slurry after the second coating of the bismuth oxychloride compound was adjusted to 75°C and the pH value was adjusted to 1.5 (the pH value was adjusted by a 14% sodium hydroxide solution by mass, and the time for adjusting the pH value from 1.0 to 1.5 was 90 minutes), 160mL of a 1.6mol / L TiCl4 solution and 28mL of a 2.0mol / L ZnCl2 solution were added to the substrate slurry after the second coating of the bismuth oxychloride compound by a constant flow pump at a uniform speed and reacted for 25 minutes (a 14% sodium hydroxide solution by mass was used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry coated with the titanium zinc compound.
[0059] The substrate slurry coated with titanium zinc compound is filtered to obtain a filter cake. The filter cake is washed with deionized water, dried in an oven at 95°C to a moisture content of 0.1%, and then calcined in a muffle furnace at 750°C for 11 minutes. The calcined material is then cooled to 20°C, washed with deionized water, and finally dried at 105°C for 3 hours to obtain a super interference iron red gold fantasy pearlescent pigment.
[0060] Example 3
[0061] 50 g of natural mica with a particle size of 120 μm was placed in a 500 mL beaker and prepared into a substrate slurry with a volume concentration of 12% with deionized water. The temperature of the substrate slurry was adjusted to 90°C and the pH value was adjusted to 0.5 (the pH value was adjusted using 15% hydrochloric acid by mass), and then 55 g of a 0.06 mol / L BiCl3 solution was uniformly added to the substrate slurry through a constant flow pump (the time for adding the BiCl3 solution was 150 min) and reacted for 35 min to obtain the substrate slurry after the first bismuth oxychloride compound was coated.
[0062] After the temperature of the substrate slurry after the first coating of the bismuth oxychloride compound was adjusted to 75°C and the pH value was adjusted to 4.0 (the pH value was adjusted by using a sodium hydroxide solution with a mass fraction of 18%, and the time for adjusting the pH value from 0.5 to 4.0 was 120 min), 25 mL of a mixture of a 1.5 mol / L MnCl2 solution and 155 mL of a 1.85 mol / L FeCl3 solution was uniformly added to the substrate slurry after the first coating of the bismuth oxychloride compound through a constant flow pump and reacted for 25 min (using a sodium hydroxide solution with a mass fraction of 18% to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry coated with the iron manganese compound.
[0063] The temperature of the substrate slurry after coating the iron-manganese compound was adjusted to 85°C, and the pH value was adjusted to 7.5 (the pH value was adjusted using a 18% by mass sodium hydroxide solution). Then, 230 mL of a 16% by mass sodium silicate solution was uniformly added to the substrate slurry after coating the iron-manganese compound through a constant flow pump to react for 35 minutes (10% by mass hydrochloric acid was used to balance the pH value of the reaction system during the coating process) to obtain the substrate slurry coated with silicon oxide.
[0064] After the temperature of the substrate slurry after coating the silicon oxide is adjusted to 95°C and the pH value is adjusted to 0.5 (the pH value is adjusted by 10% hydrochloric acid by mass, and the time for adjusting the pH value from 7.5 to 0.5 is 90 minutes), 50g of BiCl3 solution with a concentration of 0.04mol / L is uniformly added (the time for adding the BiCl3 solution is 90 minutes) to the substrate slurry after coating the silicon oxide by a constant flow pump and reacted for 35 minutes (a sodium hydroxide solution with a mass fraction of 18% is used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry after coating the second oxychloride bismuth compound.
[0065] After the temperature of the substrate slurry after the second coating of the bismuth oxychloride compound was adjusted to 65°C and the pH value was adjusted to 1.0 (the pH value was adjusted by using a sodium hydroxide solution with a mass fraction of 18%, and the time for adjusting the pH value from 0.5 to 1.0 was 120 min), 155 mL of a mixture of a TiCl4 solution with a concentration of 1.8 mol / L and a ZnCl2 solution with a concentration of 24 mL was uniformly added to the substrate slurry after the second coating of the bismuth oxychloride compound through a constant flow pump, and the mixture was reacted for 35 min (a sodium hydroxide solution with a mass fraction of 18% was used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry coated with the titanium zinc compound.
[0066] The substrate slurry coated with the titanium zinc compound is filtered to obtain a filter cake. The filter cake is washed with deionized water, and then dried in an oven at 120°C to a moisture content of 0.5%. The filter cake is then calcined in a muffle furnace at 900°C for 12 minutes. The calcined material is then cooled to 30°C, washed with deionized water, and finally dried at 110°C for 2.5 hours to obtain a super interference iron red gold fantasy pearlescent pigment.
[0067] Example 4
[0068] 45 g of natural mica with a particle size of 150 μm was placed in a 500 mL beaker and prepared into a substrate slurry with a volume concentration of 10% with deionized water. The temperature of the substrate slurry was adjusted to 82° C. and the pH value was adjusted to 2.0 (the pH value was adjusted using 13.5% hydrochloric acid by mass), and then 50 g of a 0.05 mol / L BiCl3 solution was uniformly added to the substrate slurry through a constant flow pump (the time for adding the BiCl3 solution was 130 min) and reacted for 32 min to obtain the substrate slurry after the first bismuth oxychloride compound was coated.
[0069] After the temperature of the substrate slurry after the first coating of the bismuth oxychloride compound was adjusted to 90°C and the pH value was adjusted to 3.2 (the pH value was adjusted by a 16% mass fraction sodium hydroxide solution, and the time for adjusting the pH value from 2.0 to 3.2 was 105 min), 30 mL of a 1.7 mol / L MnCl2 solution and 165 mL of a 1.9 mol / L FeCl3 solution were added to the substrate slurry after the first coating of the bismuth oxychloride compound at a uniform speed through a constant flow pump and reacted for 30 minutes (a 16% mass fraction sodium hydroxide solution was used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry coated with the iron manganese compound.
[0070] The temperature of the substrate slurry after coating the iron-manganese compound was adjusted to 80°C, and the pH value was adjusted to 9.5 (the pH value was adjusted using a 16% by mass sodium hydroxide solution). Then, 250 mL of a 14% by mass sodium silicate solution was uniformly added to the substrate slurry after coating the iron-manganese compound through a constant flow pump to react for 25 minutes (8% by mass hydrochloric acid was used to balance the pH value of the reaction system during the coating process) to obtain the substrate slurry coated with silicon oxide.
[0071] After the temperature of the substrate slurry after coating the silicon oxide is adjusted to 85°C and the pH value is adjusted to 1.5 (the pH value is adjusted by 8% hydrochloric acid by mass, and the time for adjusting the pH value from 9.5 to 1.5 is 90 minutes), 55g of BiCl3 solution with a concentration of 0.03mol / L is added at a uniform rate (the time for adding the BiCl3 solution is 70 minutes) to the substrate slurry after coating the silicon oxide by a constant flow pump and reacted for 35 minutes (a sodium hydroxide solution with a mass fraction of 16% is used to balance the pH value of the reaction system during this coating process) to obtain the substrate slurry after coating the second bismuth oxychloride compound.
[0072] After the temperature of the substrate slurry after the second coating of the bismuth oxychloride compound was adjusted to 85°C and the pH value was adjusted to 2.0 (the pH value was adjusted by a 16% mass fraction sodium hydroxide solution, and the time for adjusting the pH value from 1.5 to 2.0 was 95 minutes), a mixture of 160 mL of a 1.75 mol / L TiCl4 solution and 26 mL of a 1.8 mol / L ZnCl2 solution was uniformly added to the substrate slurry after the second coating of the bismuth oxychloride compound through a constant flow pump and reacted for 30 minutes (a 18% mass fraction sodium hydroxide solution was used to balance the pH value of the reaction system during this coating process) to obtain a substrate slurry coated with a titanium zinc compound.
[0073] The substrate slurry coated with titanium zinc compound is filtered to obtain a filter cake. The filter cake is washed with deionized water, dried in an oven at 90°C to a moisture content of 0.8%, and then calcined in a muffle furnace at 820°C for 8 minutes. The calcined material is then cooled to 25°C, washed with deionized water, and finally dried at 105°C for 3 hours to obtain a super interference iron red gold fantasy pearlescent pigment.
[0074] FWD306, FWD351 and the super interference iron red gold fantasy pearlescent pigments of Examples 1 to 4 were coated with PU resin on black and white coating cards to make comparative coating samples. Under the conditions of light source D65-10 and color measurement angle of 45°, the color was measured by using Colour The XTS colorimeter measures the sample cards, and the colorimetric data of FWD306, FWD351, and the super interference iron red and gold fantasy pearlescent pigments of Examples 1 to 4 are shown in Table 1, wherein L represents the brightness of the color card, a represents the degree of deviation of the color card from the red-green phase, and b represents the degree of deviation of the color card from the yellow-blue phase.
[0075] Table 1 Color measurement data of different super interference iron red gold fantasy pearlescent pigments
[0076] Test items L* a* b* FWD306 65.81 5.17 41.84 FWD351 64.22 4.05 38.40 Example 1 73.71 3.05 56.01 Example 2 70.79 -1.61 49.51 Example 3 71.08 2.75 52.13 Example 4 72.16 1.86 50.87
[0077] It can be seen from Examples 1 to 4 that the pigment obtained by the present invention by using a process of alternating multiple layers of high and low refractive index materials and controlling the coating amount of each layer of materials not only significantly enhances the optical interference effect, but also significantly increases the color saturation, brightness and hiding power of the pigment itself; the prepared pigment not only retains the green phase gold element in the golden pearlescent pigment, but also creates a warm atmosphere of white background and red in the golden color, so that the green phase and red phase in the golden pearlescent pigment are perfectly integrated and complement each other.
[0078] The invention coats the iron-manganese compound after mixing a MnCl2 solution and a FeCl3 solution in a certain proportion, thereby greatly shortening the process flow and saving the production cost, and at the same time, a new red-yellow hue appears in the coating process; by using BiCl3 as a raw material for coating the bismuth oxychloride compound, the pigment can obtain better glossiness; by mixing a TiCl4 solution and a ZnCl2 solution in a certain proportion and then coating the titanium-zinc compound, the process flow is greatly shortened and the production cost is saved, and at the same time, the introduction of ZnCl2 can effectively increase the hiding power and metallic texture of the product.
[0079] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a super interference iron red gold magic color pearlescent pigment, characterized in that: The substrate slurry is sequentially coated with a first bismuth oxychloride compound, an iron-manganese compound, a silicon oxide, a second bismuth oxychloride compound and a titanium-zinc compound, and the coated substrate slurry is calcined to obtain a super interference iron red gold fantasy pearlescent pigment; The iron-manganese compound coating is to add a manganese-iron mixed solution to the substrate slurry after the first bismuth oxychloride compound coating to react, the temperature of the substrate slurry after the first bismuth oxychloride compound coating is 60-90° C., the pH value is 2.0-4.0, and the reaction time is 25-35 minutes; In the manganese-iron mixed solution, the volume ratio of MnCl2 solution to FeCl3 solution is 25-35:155-195, wherein the concentration of MnCl2 solution is 1.5-1.7 mol / L, and the concentration of FeCl3 solution is 1.7-1.9 mol / L; the volume mass ratio of the manganese-iron mixed solution to the substrate slurry is 180-230 mL:40-50 g; The titanium zinc compound coating is to add the titanium zinc mixed solution to the substrate slurry coated with the second bismuth oxychloride compound for reaction, the temperature of the substrate slurry coated with the second bismuth oxychloride compound is 65-85° C., the pH value is 1.0-2.0, and the reaction time is 25-35 minutes; In the titanium-zinc mixed solution, the volume ratio of TiCl4 solution to ZnCl2 solution is 155-180:24-30, wherein the concentration of TiCl4 solution is 1.6-1.8 mol / L, and the concentration of ZnCl2 solution is 1.8-2.0 mol / L; the volume mass ratio of the titanium-zinc mixed solution to the substrate slurry is 179-210 mL:40-50 g.
2. The preparation method according to claim 1, characterized in that: The volume concentration of the substrate slurry is 7-15%.
3. The preparation method according to claim 1 or 2, characterized in that: The first bismuth oxychloride compound coating is to add BiCl3 solution to the substrate slurry for reaction, the temperature of the substrate slurry is 70-90°C, the pH value is 0.5-2.0, the concentration of the BiCl3 solution is 0.04-0.06 mol / L, the reaction time is 25-35 min, the time for adding the BiCl3 solution is 120-150 min, and the mass ratio of the substrate slurry to the BiCl3 solution is 40-50:45-55.
4. The preparation method according to claim 1 or 2, characterized in that: The silicon oxide coating is performed by adding a sodium silicate solution to a substrate slurry coated with an iron-manganese compound for reaction. The temperature of the substrate slurry coated with the iron-manganese compound is 70 to 85° C., the pH value is 7.5 to 9.5, the mass fraction of the sodium silicate solution is 12 to 16%, and the reaction time is 25 to 35 minutes. The mass volume ratio of the substrate slurry to the sodium silicate solution is 40 to 50 g: 230 to 280 mL.
5. The preparation method according to claim 4, characterized in that: The second bismuth oxychloride compound coating is to add BiCl3 solution to the substrate slurry after coating the silicon oxide for reaction, the temperature of the substrate slurry after coating the silicon oxide is 80-95°C, the pH value is 0.5-1.5, the concentration of BiCl3 solution is 0.02-0.04 mol / L, the reaction time is 25-35 min, and the addition time of BiCl3 solution is 60-90 min; the mass ratio of substrate slurry and BiCl3 solution is 40-50:45-55.
6. The preparation method according to claim 5, characterized in that: The calcination temperature is 700-900° C., and the calcination time is 8-12 minutes.
Citation Information
Patent Citations
Method for preparing gold pearlescent pigment with high hue and high brightness
CN102127321A
Preparation method of super interference gold pearlescent pigment
CN104098931A
Green phase golden pearl pigment based on synthetic mica as well as preparation method and application of green phase golden pearl pigment
CN108752978A
Cosmetic compositions containing nacreous pigments of large sized synthetic mica
CN101123938A
High saturation degree multilayer nacreous pigment and preparation thereof
CN101353488A